2009
DOI: 10.1038/ijir.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Is erectile dysfunction a predictor of cardiovascular events or stroke? A prospective study using a validated questionnaire

Abstract: Erectile dysfunction (ED) is linked to various cardiovascular risk factors and may therefore serve as a predictor of cardiovascular events. To gain further insight into this relationship, we reviewed all data regarding hospital admission for cardial or cerebral vascular disease that occurred until 2008 in a cohort of men who underwent a health investigation in 2001. Erectile function was assessed using the International Index of Erectile Function (IIEF-5) questionnaire. In total, 2506 men with a negative histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 20 publications
0
30
0
1
Order By: Relevance
“…Many epidemiologic studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have investigated the link between ED and risk of CVD, and most found a positive association. However, the magnitudes of the association varied between studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many epidemiologic studies (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have investigated the link between ED and risk of CVD, and most found a positive association. However, the magnitudes of the association varied between studies.…”
Section: Discussionmentioning
confidence: 99%
“…The key exposure variable was the presence or absence of ED at baseline. In most studies, men without ED served as the reference group, although in 3 studies (12,18,20), men with minimal or mild ED served as the reference group. We included all these studies for meta-analysis and performed a sensitivity analysis that only included studies with a reference group defined as strictly non-ED men.…”
Section: Methodsmentioning
confidence: 99%
“…Le caractère prédictif d'ECV de la DE a été démontré dans différentes populations non diabétiques [2,3] ou diabétiques [4,5]. Concernant le PEPD, il avait été suggéré mais non démontré qu'il pourrait être utile dans le dépistage des patients à haut risque cardiovasculaire.…”
Section: Discussionunclassified
“…On the other hand, higher rates of atherosclerosis and coronary artery plaque burden [9] have been reported in patients with ED, and many groups have postulated that ED may be one of the earliest signs of cardiovascular disease [10], although other recent studies have not demonstrated supporting evidence [11].…”
Section: Erectile Dysfunction In Coronary Artery Diseasementioning
confidence: 98%